Improvements to Series Elastic Actuators - Sensinger, Jonathon W.; Ff. Weir, Richard F. (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
Actuators must be safe when interacting with humans, even in unexpected situations. Safety requires low impedance (low forces for a given perturbation) at all frequencies, not only in the actuator's stable bandwidth. Series elastic actuators (SEAs) are capable of achieving low impedance across all frequencies, though their force-frequency saturation envelope is decreased as a result. This paper examines ways to increase the force fidelity of SEAs by introducing inner control feedback loops and using appropriate sensor location. Findings include the superiority of a low fidelity sensor distal to stiction sources over a high fidelity sensor proximal to stiction and the superiority of an inner position feedback loop over an inner velocity feedback loop